2019
DOI: 10.1002/cap.10073
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Guided Surgery Using Human Allogenic Bone Ring With Simultaneous Implant Placement: A Case Report

Abstract: Introduction The allogenic bone ring technique allows for horizontal and vertical bone augmentation with simultaneous implant placement in severely compromised sites. The aim of this report is to present a modified protocol for simultaneous placement of implant and allogenic bone ring graft using a computer‐guided surgery technique. Case Presentation Patient's chief complaint was to replace a missing lateral incisor. The implant site presented both vertical and horizontal tissue deficiencies. Study models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Based on previous reports, the allogeneic bone ring grafts had been used in a few clinical trials 12,13,15,33 and got sufficient bone augmentation. Still, the application of allogeneic grafts is restricted by factors such as high cost, limited sources, the risk of disease transmission, and immunologic tissue reactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous reports, the allogeneic bone ring grafts had been used in a few clinical trials 12,13,15,33 and got sufficient bone augmentation. Still, the application of allogeneic grafts is restricted by factors such as high cost, limited sources, the risk of disease transmission, and immunologic tissue reactions.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,11 In this context, increasing studies have explored simultaneous bone augmentation technique and implant placement (Bone Ring Technique) in recent years . 6,12,13 Numerous studies have demonstrated that the bone ring technique integrated with an autogenous bone block can offer excellent outcome for dimensional bone augmentation. 6,10,12,13,14,15,16 With this technique, the implant is simultaneously placed with the bone augmentation procedure which both reduces the treatment time and maintains a sufficiently stable spatial structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The template used in the present report provided a precise implementation of the digitally determined implant position [ 5 , 9 11 , 15 , 16 ]. The navigated procedure offered further advantages by eliminating the need for intraoperative flap formation, thus reducing surgical trauma and reducing the postoperative need for analgesics [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%